Fatwa klausul sanksi dalam akad: studi komparatif fatwa Dewan Syariah Nasional (DSN) Majelis Ulama Indonesia (MUI) dan Majma Fiqh Organisasi Konferensi Islam (OKI) - Zawawi Zawawi (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2016)
Delaying obligation payment by the customer to the syariah financial institution in some countrieswhose moslem as the majority, need solutions. One of them is determining Islamic organization fatwa.International Islamic Fiqh Academy has declared fatwa of retributive condition of prohibition based onthe agreement between the bank and the customer, while Sharia Directory of Indonesia permits this.Problem of this research is how the concept of retributive condition in those two organizations is andwhat method used in determining fatwa of the retributive condition is. This research used qualitativeapproach based on library research, while type of this research is comparative descriptive by usingistislahi approach. The result shows that there is significant difference between fatwa from InternationalIslamic Fiqh Academy and Sharia Directory of Indonesia in determining the kind of contrac, that canaccept retributive condition based on International Islamic Fiqh Academy, fine can not be applied in ancontrac which causes obligation, such as salam, transaction of installments and qard. Sharia Directory ofIndonesia decides that fine clause can be applied to any contrac which causes obligation. Determiningfatwa from majma fiqh uses saddu dzariah approach by giving attention to the carefulness norms inconsideration of maslahat and mafsadat. On the other side, Sharia Directory of Indonesia uses istislahimethod which puts maslahat as the priority, especially for syariah financial organizations.